2008
DOI: 10.1007/s10661-008-0629-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of temporal variations of water quality in inland water bodies using atmospheric corrected satellite remotely sensed image data

Abstract: Although there have been many studies conducted on the use of satellite remote sensing for water quality monitoring and assessment in inland water bodies, relatively few studies have considered the problem of atmospheric intervention of the satellite signal. The problem is especially significant when using time series multi-spectral satellite data to monitor water quality surveillance in inland waters such as reservoirs, lakes, and dams because atmospheric effects constitute the majority of the at-satellite re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 28 publications
0
34
0
2
Order By: Relevance
“…Remote sensing techniques have been extensively used for monitoring chl-a in aquatic systems [4,[8][9][10]. The advantages of using remote sensing techniques to monitor chl-a are: (1) the geographical coverage of satellite images, which provide information about the entire aquatic system; (2) remote sensing, which allows us to obtain information from inaccessible places; and (3) historical satellite images, which allow the inference of water quality information from the past records [11]. Thus, remote sensing can provide a regional and constant tool to monitor the spatial and temporal variability of water quality parameters, which is supported by Gons [7], who observed that the use of remote sensing techniques was a time saving, cost-effective and scientifically rewarding alternative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing techniques have been extensively used for monitoring chl-a in aquatic systems [4,[8][9][10]. The advantages of using remote sensing techniques to monitor chl-a are: (1) the geographical coverage of satellite images, which provide information about the entire aquatic system; (2) remote sensing, which allows us to obtain information from inaccessible places; and (3) historical satellite images, which allow the inference of water quality information from the past records [11]. Thus, remote sensing can provide a regional and constant tool to monitor the spatial and temporal variability of water quality parameters, which is supported by Gons [7], who observed that the use of remote sensing techniques was a time saving, cost-effective and scientifically rewarding alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for estimating chl-a concentration in different turbid waters (Case 2) with remote sensing have been investigated [4][5][6][7][8][9][10][11][12]. Many studies have suggested that remote spectroscopic measurements from the Moderate Resolution Imaging Spectroradiometer (MODIS) should be used to estimate chl-a concentrations in Case 2 waters through empirical and semi-empirical algorithms [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…An important radiometric correction is the atmospheric correction which can be easily applied using image-based atmospheric corrections techniques, such as the simplest one, the DP algorithm. Most published atmospheric correction methods have been developed for specific targets, such as, coastal and inland waters or land, and their effectiveness for other targets and different applications needed first to be assessed [21,45,46]. Indeed, an example of how important the atmospheric correction is, for archaeological research, especially when NDVI's are used for archaeological crops detection, is shown in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Field spectroscopy has previously been applied to obtain radiance, irradiance and reflectance values of freshwater, sea-water and pure water [1][2][3][4][5][6][7][8][9][10][11][12]. Spectrometers or spectro-radiometers are widely used to collect spectral data [13].…”
Section: Introductionmentioning
confidence: 99%